Hubungan Membaca Label Pangan terhadap Pemilihan Makanan Kemasan pada Mahasiswa Gizi Universitas IVET Semarang - Chairunisa Nur Rarastiti; Santy Sundari (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
One of Pedoman Gizi Seimbang points, advise consumers to get used reading food labels on packaged food. This is the way to choose products that are safe and healthy. Consumptive behavior towards packaged food products is now increasingly widespread, especially among college students. However, the information listed on food labels is often ignored. Nutrition students are expected to be able to implement knowledge by reading food labels when choosing each product that is purchased and consumed. This study aims to determine the relationship between reading food labels and packaged food choice for nutrition students of IVET University Semarang. Design of this research is cross sectional and the number of samples are 37 respondents. Respondent data was obtained by filling out questionnaires including age, gender, questions about reading food labels and packaged food choice. The results showed that there was a relationship between reading food labels and packaged food choice for nutrition students at IVET University Semarang (p=0.000; r=0.644). When choosing a food product, most respondents pay attention to the expiration date, total energy and food composition. Food safety is an important aspect that must be considered. Safe, nutritious and quality plays an important role for public health status.